Impact of the Physical Environment in Paediatric Hospitals on Health Outcomes: a Systematic Review - Watts, Robin; Wilson, Sally (University of Adelaide, 2009)
Objectives. The objective of this review was to determine from the available evidence the impact of the physical paediatric hospital environment on health outcomes of children and adolescents.